Basic Economic Analysis for Sonochemical Processes - Carlo Pirola (Journal of Chemical Engineering Research Updates, 2020)
Ultrasound (US) and other non-traditional energy sources (for instance microwave (MW)) are widely used to increase the rate of chemical reactions, to prepare nanoparticles, to extract natural products etc. In all such cases, the scaling-up of the process must have a defined economic constraint, which generally can be reduced to the evaluation of the parameter RC, which is the ratio between the raw energy cost to produce US (or MW) and the total production cost for unit mass of product. The paper gives a basic correlation among the different parameters to evaluate RC both for processes using only US (or MW and other not traditional sources) and those with mixed energy sources.